Organizational structure of construction companies in the function of their efficient operation - Kedioski Vlatka; Lazarevska Marijana; Gacevski Vasko; Ristov Riste (UNIVERSITY OF MONTENEGRO FACULTY OF CIVIL ENGINEERING, 2024)
The organizational structure of the construction company represents the structure and the management of the project team, goods and project resources. It is a fundamental aspect of project management that defines how activities are coordinated and controlled in order to achieve the planned project and company goals. Companies that are in construction business have organizational structures that are based on project management. Construction projects are usually complex, capital, unique and unrepeatable. Project management is the application of knowledge, tools, techniques, and systems to define, execute, measure, control, report and improve processes. This paper explains several aspects that should be considered when choosing the organizational structure of the construction company. Nine case studies of medium and large construction companies were analysed, where special emphasis is placed on the types of organizational structure used, their complexity, adaptability, integrative processes, control during work, description of processes and procedures, etc. The results of conducted analysis showed that 56% of the analysed companies use a composite organizational structure, while the remaining 44% use a functional organizational structure. Although the analysed companies implement "Projects", they very rarely use a project organizational structure, and when they do it is mostly for some large and complex projects that are being implemented outside our country. By understanding the importance of the organizational structure, when the right one is chosen, high management and project managers can improve the overall project outcomes and increase the likelihood of success.
Keywords: construction projects, organizational structure, project management